The Influence of Using Tiktok Application on the Establishment of Student Entrepreneurial Spirit - Sari, Kharisma Harum; Supriadi, Acep; Rakhman, Muhammad Arief (UNDIKMA, 2024)
TikTok is the most popular social media in Indonesia with an average usage duration of more than 2 hours per day with a percentage of 47.4% from Indonesian population. TikTok initially only functioned as an entertainment media by displaying various short videos. However, along with its development, TikTok now opens up great opportunities for business owners to be able to expand their marketing through video advertisements. This study aims to determine the influence of using TikTok on the establishment of student Entrepreneurial Spirit of Social Science Education students. The approach used is a quantitative approach with a survey method. This study involved 162 respondents as a sample using the Proportionate Stratified Random Sampling technique. The data collection technique used in this study was a questionnaire with a Likert scale. Hypothesis testing in this study using simple linear regression analysis. The results showed a sig value. 0.008 <0.05 and obtained a t-count value of 2.685> t-table 1.975, which means that there is a positive influence between the two variables.